Infectious Rous Sarcoma Virus and Reticuloendotheliosis Virus DNAs - Cooper, Geoffrey M. (1974)
An efficient and quantitative assay for infectious Rous sarcoma virus and reticuloendotheliosis virus DNAs is described. The specific infectivities of viral DNA corresponded to one infectious unit per 10(5) to 10(6) viral DNA molecules. Infection with viral DNA followed one-hit kinetics. The minimal size of infectious Rous sarcoma virus DNA was approximately 6 million daltons, whereas the minimal size of infectious reticuloendotheliosis virus DNA was larger, 10 to 20 million daltons.